Impact of biodiesel application on fuel savings and emission reduction for power generation in Malaysia - Tan E.S.; Kumaran P.; Indra T.M.I.; Tokimatsu K.; Yoshikawa K. (Elsevier Ltd, 2023)
Biodiesel; Carbon dioxide; Combustion; Economic analysis; Electric utilities; Emission control; Fuel economy; Gas turbines; Neutron emission; Power generation; Carbon dioxide emissions; Economic growths; Economic indicators; Economic performance; Emission reduction; Independent power producers; Properties; Transport sectors; Electric power system economics